Activated low-density granulocytes in peripheral and intervillous blood and neutrophil inflammation in placentas from SLE pregnancies. Issue 1 (8th March 2021) - Stockfelt, Marit; Larsson, Gunilla; Engström, Hanna; Puttonen, Henri; Zetterberg, Henrik; Blennow, Kaj; Sjöwall, Christopher; Strevens, Helena; Jönsen, Andreas; Bengtsson, Anders A; Majczuk Sennström, Maria; Zickert, Agneta; et al.
Abstract : Objective: Women with SLE face an increased risk of adverse pregnancy outcomes compared with healthy women, but the underlying immunological mechanisms are unknown. Given the recognised association of neutrophil activation with SLE pathogenesis, we examined whether there is increased neutrophil activation and inflammation in blood and placenta in SLE relative to healthy pregnancy. Methods: At delivery, peripheral blood, maternal-derived intervillous blood and placentas were collected from 12 SLE and 10 healthy control pregnancies. The proportion of low-density granulocytes (LDGs) and the activation status of LDG and normal-density granulocytes were examined with flow cytometry. The chemokines CXCL8 and CXCL1 were quantified with a cytometric bead-based assay and interferon alpha (IFNα) protein levels with a Simoa method. IFNα-stimulated maternal-derived decidual stromal cells were examined for CXCL8 gene expression with qPCR. A pathologist, blinded to the patient background, examined all placentas. Results: Women with SLE had significantly higher proportions of LDG in peripheral blood compared with controls (p=0.02), and LDG in both peripheral and intervillous blood were more activated in SLE relative to healthy pregnancies (peripheral blood: p=0.002 and intervillous blood: p=0.05). There were higher levels of CXCL8 and CXCL1 in intervillous compared with peripheral blood in women with SLE (p=0.004 and p=<0.0001, respectively) but not in controls. In SLE pregnancy, IFNα was detectable in 6 out of 10 intervillous blood samples but only in one control. Stimulation with IFNα upregulated CXCL8 gene expression in decidual stromal cells from both SLE and healthy pregnancy. Histological chorioamnionitis was present in 6 out of 12 placentas from women with SLE and in 1 out of 10 controls. Conclusions: In women with SLE, locally produced chemokines in the placenta are increased and may attract and activate neutrophils. This in turn could contribute to placental inflammation and dysfunction and increased risk of placenta-related pregnancy complications.